Analisis Kegiatan Pembelajaran Mengenal Huruf Anak Usia 4-5 Tahun - Bernadetha Asni; Hariani Fitrianti; Nurlayli Hasanah; Minuk Riyana (Musamus Journal of Primary Education, 2022)
This study aims to analyze learning activities to recognize letters for children aged 4–5 years. The type of research used is qualitative research. The research method used is literature study or literature study. The sources of data used are journals related to early childhood learning activities. The instrument in this research is the researcher himself (human instrument). The subjects of this study were kindergarten children aged 4–5 years. Data analysis was carried out in 3 stages, namely data reduction, data presentation, and conclusion drawing. The results of the study explain that learning activities to recognize letters in children aged 4–5 years are carried out through learning media, including learning activities through letter cards, learning activities through image media, learning activities through flashcard media, learning activities through letter puzzles, learning activities through media, sandpaper letters, and alphabet jumping games. This shows that children are more interested in learning when using modified card media in learning, especially for children aged 4-5 years to recognize letters. This is evidenced from the 10 journals studied using the modified card media that can improve the ability to recognize letters in children aged 4-5 years. Based on the results of the study, it was concluded that learning activities to recognize letters in early childhood 4-5 years can be done through letter card media innovation